Cryoprotection and banking of living cells in a 3D multiple emulsion-based carrier. - Dluska, E; Cui, Z; Markowska-Radomska, A; Metera, A; Kosicki, K (Wiley, 2017)
The ability to preserve stem cells/cells with minimal damage for short and long periods of time is essential for advancements in biomedical therapies and biotechnology. New methods of cell banking are continuously needed to provide effective damage prevention to cells. This paper puts forward a solution to the problem of the low viability of cells during cryopreservation in a traditional suspension and storage by developing innovative multiple emulsion‐based carriers for the encapsulation and cryopreservation of cells. During freezing‐thawing processes, irreversible damage to cells occurs as a result of the formation of ice crystals, cell dehydration, and the toxicity of cryoprotectant. The proposed method was effective due to the “flexible” protective structure of multiple emulsions, which was proven by a high cell survival rate, above 90%. Results make new contributions in the fields of cell engineering and biotechnology and contribute to the development of methods for banking biological material.